An architecture for co-evolving agents in the ROBOCUP Simulation League - Rocha, Miguel (2004)
In H. Coelho and B. Espinasse (Eds.), Proceedings of 5th Workshop on Agent-Based Simulation, pp. 127-132, Lisbon, Portugal, May, 2004. SCS.